PENGEMBANGAN E‑MODUL BAHASA ARAB BERBASIS KURIKULUM MERDEKA - Ana Sofia; Asmaul Husna; Siti Rahmah (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
The development of digital technology has driven the need for innovative teaching materials that are adaptive, interactive, and learner-centred. This study aims to develop an Arabic e-module based on the Merdeka Curriculum that meets the criteria of being valid, practical, and effective in supporting the learning process. This study uses the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved subject matter experts, media experts, Arabic teachers, and secondary school students. Data were collected through validation sheets, practicality questionnaires, and learning outcome tests. The validation results showed that the e-module was of excellent quality in terms of content, language, and media display. The practicality test showed that the e-module was easy to use, interesting, and helped students learn independently. In addition, the effectiveness test results showed an increase in student learning outcomes after using the e-module. Based on these results, it can be concluded that the Arabic e-module based on the Merdeka Curriculum is suitable for use as digital teaching material and can be an innovative alternative to improve the quality of Arabic language learning.